2013
DOI: 10.1177/1088767913497949
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Fatality Reviews and the African American Community

Abstract: Cultural competence is important to the domestic violence fatality review process. This article reviews current knowledge about cultural competence for Black women abused by men in the United States, with suggested implications for domestic violence fatality review teams (DVFRTs). Help-seeking behaviors, coping strategies, historical context, and cultural values within the African American community are explored. These areas are further examined using a framework inclusive of the structure, goals, processes, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 28 publications
(31 reference statements)
1
53
0
Order By: Relevance
“…Having such research is critical. With women of color being more likely to be victimized and killed due to domestic violence (Bent-Goodley, 2013; Smith et al, 2017; Violence Policy Center, 2017), the need for having effective interventions rooted in the realities of these communities could not be more important. Scholars have an enormous responsibility to get this right to advance IPV knowledge generation and to move the science forward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having such research is critical. With women of color being more likely to be victimized and killed due to domestic violence (Bent-Goodley, 2013; Smith et al, 2017; Violence Policy Center, 2017), the need for having effective interventions rooted in the realities of these communities could not be more important. Scholars have an enormous responsibility to get this right to advance IPV knowledge generation and to move the science forward.…”
Section: Discussionmentioning
confidence: 99%
“…Being able to understand the worldview of the group allows you to build more accuracy to determining problem definition (Burnette, 2016). For example, it is important to understand that when working with Black women who have experienced domestic violence, they may be concerned with how reporting domestic violence makes Black men vulnerable to criminal justice intervention (Bent-Goodley, 2013). In addition, Black women have been socialized to protect Black men as a part of a survival tradition in the Black community (Richie, 1995).…”
Section: Literature Review and The Importance Of Worldviewmentioning
confidence: 99%
“…While Black men who were killed (50.0%) were slightly more likely to be complainants than White men (42.9%), Black women who were killed (32.1%) were slightly less likely to be complainants than White women (33.3%). These disparities may reflect over-policing in African American communities as well as the manner in which African American women are perceived by police officers (Bent-Goodley, 2013;Hitchens, Carr, & Clampet-lundquist, 2018;Richie, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The analyses of race suffer from a lack of specificity due to the nature of police-report data; the dichotomous Black/White categorization is particularly problematic given, for example, the "racialization of legal status" among Latinos (Menjívar, Simmons, & Alvord, 2018, p. 111). We have nevertheless included these data, given previous research indicating differential homicide rates across race/ethnicity and the context of over-policing in communities of color, fear of police, and differential treatment of victims and offenders based on race/ethnicity (Bent-Goodley, 2013;Hitchens et al, 2018;Petrosky et al, 2017;Richie, 2012). Finally, in subgroups of the data that were examined, some categories of homicide had a rather small sample sizes, and these findings should be interpreted with caution.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…St Vil and colleagues (2017) found that Black women utilized three types of survivor strategies: internal strategies of faith and reli-gion, interpersonal strategies of leaving the abuse, and external reliance on informal and/or formal supports. Many Black women reported relying on the church community and friends and family for support, while only some looked for support from organizations that specialized in supporting women who experience IPV (Bent-Goodley 2013;St Vil et al 2017). Other studies indicate that although Black women are hesitant to use legal resources, they are more likely to access them when there is a high risk for lethality (Sabri et al 2014).…”
Section: Black Women Seeking Support For Ipvmentioning
confidence: 99%